THERMAL AND ENERGY ANALYSIS OF AN ICE-MAKING MACHINE USING AN OUTDOOR AC REFRIGERATION SYSTEM - Reinaldi Teguh Setyawan; Irwan Kurniawan; Siti Umira (Department of Mechanical Engineering Education, 2025)
This study investigates the thermal and energy performance of a custom designed ice maker that utilizes a modified outdoor air conditioning (AC) unit as its primary refrigeration system. The objective is to evaluate the feasibility, efficiency, and operational stability of using a household AC condenser unit for small scale ice production, particularly in areas with limited access to commercial ice making equipment. The experimental setup was tested over an 8 hour operation period, with parameters such as input water temperature, ice formation temperature, freezing time, power consumption, Coefficient of Performance (COP), and system efficiency being measured and analyzed. The results show that the system was capable of producing 6.5 kg of ice, with a measured actual COP of 3.05 and an efficiency of 67.78%. Although minor deviations were observed from the design specifications, the overall performance remained within acceptable limits. These findings suggest that repurposing outdoor AC units can provide a cost effective and energy efficient alternative for localized ice production.